Non-invasive brain stimulation in the modulation of cerebral blood flow after stroke: A systematic review of Transcranial Doppler studies. Issue 12 (December 2018) - Iyer, Pooja C.; Madhavan, Sangeetha
Highlights: Cerebral hemodynamics of non-invasive brain stimulation using TCD is less explored. Cerebral blood flow velocity changes in response to rTMS and tDCS. Need for a more standardized approach with future studies. Abstract: Objective: Non-invasive brain stimulation (NIBS), such as repetitive TMS (rTMS) and transcranial direct current stimulation (tDCS), are promising neuromodulatory priming techniques to promote task-specific functional recovery after stroke. Despite promising results, clinical application of NIBS has been limited by high inter-individual variability. We propose that there is a possible influence of neuromodulation on cerebral blood flow (CBF), as neurons are spatially and temporally related to blood vessels. Transcranial Doppler (TCD), a clinically available non-invasive diagnostic tool, allows for evaluation of CBF velocity (CBFv). However, little is known about the role of neuromodulation on CBFv. Methods: A systematic review of literature to understand the effects of NIBS on CBFv using TCD in stroke was conducted. Results: Twelve studies fit our inclusion criteria and are included in this review. Our review suggested that CBFv and/or vasomotor reactivity maybe influenced by rTMS dosage (intensity and frequency) and the type of tDCS electrode montage. Conclusion: There is limited evidence regarding the effects of NIBS on cerebral hemodynamics using TCD and the usefulness of TCD to capture changes in CBFv after NIBS is not evident from this review. We highlight the variability in the experimental protocols, differences in the applied neurostimulation protocols and discuss open questions that remain regarding CBF and neuromodulation. Significance: TCD, a clinically accessible tool, may potentially be useful to understand the interaction between cortical neuromodulation and CBFv.